2018
DOI: 10.1016/j.cub.2018.06.048
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule-Associated Protein CLASP Sustains Cell Proliferation through a Brassinosteroid Signaling Negative Feedback Loop

Abstract: The capacity for sustained cell division within the plant meristem is a critical determinant of organ structure and performance. This capacity is diminished in mutants lacking the microtubule-associated protein CLASP and when brassinosteroid signaling is increased. Here, we discovered that CLASP is both targeted by and promotes activity of the brassinosteroid pathway in Arabidopsis root apical meristems. We show that enhanced brassinosteroid signaling reduces CLASP transcript and protein levels, dramatically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 74 publications
(118 reference statements)
1
54
0
Order By: Relevance
“…When plants were deprived of light and a source of sucrose, the auxin transporter PIN2 and BR receptor BRI1 were less abundant at the plasma membrane and accumulated in the vacuole. This redistribution is consistent with a lack of CLASP, which normally promotes recycling of PIN2 and BRI1 to the plasma membrane through tethering of SNX1 vesicles (Ambrose et al, 2013; Ruan et al, 2018). Cells in the division zone of roots normally have several small vacuoles, whereas an enlarged central vacuole is characteristic of elongating and differentiated cells.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…When plants were deprived of light and a source of sucrose, the auxin transporter PIN2 and BR receptor BRI1 were less abundant at the plasma membrane and accumulated in the vacuole. This redistribution is consistent with a lack of CLASP, which normally promotes recycling of PIN2 and BRI1 to the plasma membrane through tethering of SNX1 vesicles (Ambrose et al, 2013; Ruan et al, 2018). Cells in the division zone of roots normally have several small vacuoles, whereas an enlarged central vacuole is characteristic of elongating and differentiated cells.…”
Section: Discussionsupporting
confidence: 73%
“…Previous work has shown that CLASP promotes recycling of the BRI1 receptor (Ruan et al, 2018) and PIN2 transporter (Ambrose et al, 2013) to the plasma membrane. Since CLASP protein levels were depleted in dark-grown seedlings, we hypothesized that the distribution and abundance of BRI1 and PIN2 would be affected in light-versus dark-grown seedlings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations